2017
DOI: 10.1111/jbg.12285
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of inbreeding depression on female fertility in the Finnish Ayrshire population

Abstract: Single nucleotide polymorphism (SNP) data enable the estimation of inbreeding at the genome level. In this study, we estimated inbreeding levels for 19,075 Finnish Ayrshire cows genotyped with a low-density SNP panel (8K). The genotypes were imputed to 50K density, and after quality control, 39,144 SNPs remained for the analysis. Inbreeding coefficients were estimated for each animal based on the percentage of homozygous SNPs (F ), runs of homozygosity (F ) and pedigree (F ). Phenotypic records were available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 19 publications
(47 reference statements)
10
42
3
2
Order By: Relevance
“…No animal experiments were carried out for this study, and therefore ethical approval was not required. The genotypic data used in this study were the same as in Martikainen et al 5 and were obtained from the Nordic Cattle Genetic Evaluation (NAV) (Aarhus, Denmark). The original genotypes of 19,075 Finnish Ayrshire females were derived from the Illumina BovineLD v.2 BeadChip low-density panel 22 , which contains 7,931 SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…No animal experiments were carried out for this study, and therefore ethical approval was not required. The genotypic data used in this study were the same as in Martikainen et al 5 and were obtained from the Nordic Cattle Genetic Evaluation (NAV) (Aarhus, Denmark). The original genotypes of 19,075 Finnish Ayrshire females were derived from the Illumina BovineLD v.2 BeadChip low-density panel 22 , which contains 7,931 SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…Using only pedigree information, Cassell et al (2003) observed an undesirable but nonsignificant effect of maternal and fetal inbreeding on 70-d nonreturn rate for Holsteins across parities, whereas a significant and undesirable effect of maternal inbreeding for Jerseys was found to cause a 3% reduction in 70-d nonreturn rate per 10% increase in inbreeding. Martikainen et al (2017) found significant evidence of inbreeding depression on female fertility in Finnish Ayrshire (0.5-d interval from first to last insemination in heifers and first-parity cows, 1.4-d interval from first to last insemination in 2+ parity cows, and 0.3-d interval from calving to first insemination per 1% increase in F j G ) but only using genomic information (pedigreebased inbreeding coefficients did not show inbreeding depression in any of the traits analyzed).…”
Section: Reproduction and Fertility Traitsmentioning
confidence: 99%
“…This analysis demonstrated that the KY12 population sample exhibited a significantly higher mean F ROH value than the KY92 population sample ( P adjust = 0.0340). This is important from a conservation genetics perspective, indicating that genome-wide autozygosity, which is highly correlated with conventional pedigree-based estimates of inbreeding ( F PED ) for cattle (Purfield et al, 2012; Ferenčaković et al, 2013; Martikainen et al, 2017), has increased for the Kerry cattle population in the 20 years between sampling of the KY92 and KY12 populations.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of understanding and quantifying genome-wide autozygosity for genetic conservation purposes has recently been highlighted through correlation of F ROH with inbreeding depression for a range of production traits in domestic cattle (Bjelland et al, 2013; Pryce et al, 2014; Kim et al, 2015). Importantly, F ROH has also been shown to correlate with inbreeding depression for bovine fertility traits in both males (Ferencakovic et al, 2017) and females (Kim et al, 2015; Martikainen et al, 2017). Finally, according to basic population genetic principles, recent inbreeding captured by F ROH will lead to recessive deleterious genomic variants emerging at a population level— a phenomenon that has been studied in both humans and cattle (Szpiech et al, 2013; Zhang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%